2023
DOI: 10.1007/s10389-023-01884-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a risk score to identify patients at high risk for a severe course of COVID-19

Abstract: Aim We aimed to develop a risk score to calculate a person’s individual risk for a severe COVID-19 course (POINTED score) to support prioritization of especially vulnerable patients for a (booster) vaccination. Subject and methods This cohort study was based on German claims data and included 623,363 individuals with a COVID-19 diagnosis in 2020. The outcome was COVID-19 related treatment in an intensive care unit, mechanical ventilation, or death after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Immune senescence and underlying comorbidities make older adults generally more susceptible to COVID-19 and associated severe outcomes. Several studies have identified older age as a primary risk factor for severe illness with COVID-19 (6,7,8), with one study demonstrating similar performance between a risk score that was based on age alone versus a validated risk score incorporating the effects of multiple underlying comorbidities (POINTED score) (9). Importantly, the WHO has identified older adults (commonly defined by age cutoffs of 50 to 60 years, depending on the country) as a high-priority group for COVID-19 vaccination (10), and many countries have prioritized vaccination of the older population (9).…”
Section: Introductionmentioning
confidence: 99%
“…Immune senescence and underlying comorbidities make older adults generally more susceptible to COVID-19 and associated severe outcomes. Several studies have identified older age as a primary risk factor for severe illness with COVID-19 (6,7,8), with one study demonstrating similar performance between a risk score that was based on age alone versus a validated risk score incorporating the effects of multiple underlying comorbidities (POINTED score) (9). Importantly, the WHO has identified older adults (commonly defined by age cutoffs of 50 to 60 years, depending on the country) as a high-priority group for COVID-19 vaccination (10), and many countries have prioritized vaccination of the older population (9).…”
Section: Introductionmentioning
confidence: 99%